Balance of migration in Belarus: positive or negative? - Zlotnikov, Anatoly G. (Journal of the Belarusian State University. Sociology, 2019)
The features of migration of modern Belarus are regarded. The role of the national censuses of 1999 and 2009 years in determining the true extent of international migration in Belarus is proved. The characteristic vectors of migration the population of Belarus is given. The influence of the Belarusian labor migration on demographic processes in the country are shown. The contradictions and problems of Belarusian of migration are analyzed. The influence of Belarusian migration on the prospects of demographic development of the country is considered.
Keywords: migration; international migration; return migration; demographic development; labor migration; Belarusian migration; expats; contradiction of the Belarusian migration